Prevalence and antimicrobial resistance of methicillin resistant Staphylococcus epidermidis isolated at Mymensingh Medical College Hospital (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):163-9.The abstract of this article is available on the PubMed website